Estimasi Nilai Heritabilitas Lingkar Dada dan Panjang Badan pada Kambing Peranakan Etawah di BPTU dan HPT Pelaihari Kalimantan Selatan - M. F. Amin; G. Ciptadi; V. M. A. Nurgiartiningsih (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2021)
Evaluation in standardization really needs to be carried out, including whether the livestock is in accordance with the SNI vital statistics standard (Indonesian national standard). The purpose of the study was to estimate heritability and breeding values of body weight and vital statistics in Etawah Grade (PE) goats in BPTU and HPT Pelaihari Kalimantan Selatan. The material used were the performance records of 220 PE goats, offsprings of 35 males and 71 females. The variables measured were body length and chest girth at birth, weaning, and 1 year of age. Variance componenet were analyzed using variance analysisrade. Heritability was estimated using the paternal half-sib correlation method by applying SPSS software. Breeding value was estimated using the progeny test model. The highest breeding value on body length at birth, at weaning age and at 1 year of age were sire 3315 KK, sire 4093 OK, and sire 4007 OK, respectively. The highest breeding Value on chest girth at birth, weaning age and 1 year of age were sire 3983 HH, 3315 HH, and 3971 HH. The conclusion of this study were the heritability for body weight were categorized high and for statistic vital were varied from medium to high value.